Influ??ncia dos atributos dos stakeholders no sucesso do portf??lio de projetos - Banzato, Carlos Roberto (2019)
An organization that have a Project portfolio aligned with the demands from the market and of its stakeholders will own a powerful ???weapon??? that must be considered as the central pillar for implementing its strategy. Organizations that can rely on its stakeholders' management capabilities define and implement communication processes, deal with critical issues, try to reach voluntary agreements, integrate borders for the strategy formulation processes, are proactive, allocate resources accordingly with their concerns and have leaders whose mindset is focused on serving the stakeholders. The thesis objective was to study the influence of stakeholders attributes on project portfolio management phases and project portfolio success. The thesis proved the influence of stakeholders' attributes on project portfolio management phases and on project portfolio success. The research showed a model linking Stakeholders' attributes, Project portfolio management phases and Project portfolio success. Concrete actions were proposed by the executives based on the research findings. Regarding the contributions we point out academic contributions using the proposed model to proceed qualitative and quantitative researchs and management contributions focused on the organizations benefits using the stakeholders identification to execute the strategy successfully.